'Straight? What straight?'Investigating navigation instructions'applicability. (2nd January 2023) - Teimouri, Fateme; Richter, Kai-Florian
ABSTRACT: Anecdotal evidence shows that, sometimes, the instructions generated by a navigation service do not seem to match with how a wayfinder understands the given wayfinding situation. Such issues may make processing instructions harder for the wayfinder, and it may be a potential source of wayfinding errors and dangerous behaviour. These mismatches may be caused by several issues, ranging from errors in the base data to issues with the instruction generating system – the service's inference system. In this work, we focus on the latter. We empirically investigate how much people agree with navigation instructions usefully describing a given wayfinding situation. To this end, we collected both quantitative (ratings) and qualitative data (comments and alternative instructions). Quantitative analysis supports the assumption that, sometimes, instructions just do not seem to fit. Qualitative analysis points to two main sources for the mismatches: 1) the language used in the instructions; 2) how the navigation service represents and reasons about a wayfinding situation.